Early childhood intervention: the Portuguese pathway towards inclusion - Serrano, Ana Maria (2011)
This article describes the Early Childhood Intervention (ECI) system in Portugal and how it evolved since the 80’s until our days, based on a set of principles recommended by research and empirical data. So it describes the characteristics, organization and legislation and implementation of the ECI Portuguese system which pertain to be an inclusive and community resource based early intervention system.